Global sourcing and technical efficiency – a firm-level study on the ICT industry in Sweden - Andersson, Martin; Stone, Trudy-Ann (Journal of Business Economics and Management, 2017)
We analyse the relationship between international sourcing, measured as imports of intermediate inputs, and the technical efficiency of firms in the information and communications technologies (ICT) manufacturing industry in Sweden. Using stochastic frontier analysis, we provide evidence that global sourcing improves firms’ capabilities to combine and re-combine inputs in productive ways, thereby increasing technical efficiency. We find a robust relationship between technical efficiency and international outsourcing. First, we find that firms that are deeply integrated into global sourcing networks are closer to their own production frontier. Second, firms that are engaged in international sourcing are also closer to the industry efficiency frontier. These findings are consistent with the argument that international sourcing stimulates firms’ capabilities by enabling them to identify and adopt higher quality inputs or more efficient production and management practices. These findings also suggest that the variety and extent of firms’ global sourcing networks constitute an important source of differences in efficiency levels among firms the ICT manufacturing industry.